FAKTOR DEMOGRAFI, FINANCIAL TECHNOLOGY, DAN KINERJA KEUANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM): INKLUSI KEUANGAN SEBAGAI MEDIASI - Suyanto Suyanto (AKUNTANSI DEWANTARA, 2022)
This study aims to examine the influence of demographic factors and financial technology on the financial performance of micro, small and medium enterprises (MSMEs) and the mediating role of financial inclusion. This quantitative study uses a descriptive approach. The population in this study is SMEs in Yogyakarta, Indonesia. The sample in this study is This study consisted of 108 respondents. This test was conducted using multiple linear regression analysis and path analysis. This study considers the effectiveness of the application of financial inclusion as a factor that mediates the influence of demography and financial technology on the performance of MSMEs in Yogyakarta City. The results of this study prove that demographic factors does not affect financial inclusion, financial technology has a positive effect on financial inclusion, demographic factors have a positive effect on financial performance, financial technology has no effect on financial performance, financial inclusion has a positive effect f on financial performance. Demographic factors affect financial performance through financial inclusion and financial technology affects financial performance through financial inclusion. Keywords : Demographic Factors, Financial Technology, Financial Performance, Financial Inclusion